Perancangan Aplikasi Data Mining Untuk Mempolakan Penjualan Pada Basoka Motor - Shevti Arbekti Arman (ITB Ahmad Dahlan Jakarta, 2023)
Basoka Motor in its marketing activities is still done manually and has not yet idolized the sale of its motorbikes with the support of information technology. Designing an application can see the sales patterns that occur at Basoka Motor. To get information, one of the classification methods used in data mining is the decision tree method using the C.45 algorithm. Tests conducted between manual calculations and data mining applications on 27 motorcycle data obtained from Basoka Motor get the same results with an accuracy level of 100% using Confusion Matrix. Application development using the waterfall method with testing, namely Black Box Testing.